Legal Awareness And Legal Culture As Elements And Means For The Implementation Of A Mechanism For Ensuring The Legal Impact - Michailowna Drozdova, Alexandra; Mikhailovna Balakireva, Lidiya; Victorovna Vorotilina, Tatyana; Vitalyevna Makarova, Elena; Vedeniktovich Meleshkin, Valery (Opción, 2019)
The article is concerned with the theoretical understanding of the problems in the field of analysis of the elements of the mechanism for ensuring the legal impact, while studying the mechanism of impact of the law on people’s behavior under the influence of various social norms, especially if the content of all or some of them coincide in their requirements. The author analyzes modern legal and conceptual aspects of the essence of legal consciousness in conjunction with legal culture, presented in the form of traditions, customs, legal customs, morality, values, ideas of justice, collectivism, respect, mutual assistance, the priority of social interests, respect for law and the state, which should be inherent to every nation. Certain problems, shortcomings, and contradictions in the development of modern Russian legal theory and doctrine in the field of improvement of the legal impact and regu- lation mechanism are identified; it is stated that since the beginning of its creation, the legal norm has had not only a regulatory effect but also an educational one, preventive, proactive, protective, etc., which must be used in practice. The thesis is considered that ideas or laws alone are insufficient for effective legal regula- tion, since simultaneous changes in legal consciousness and culture are required. The informative function of law, based on the promotion of legal norms and legal education, is pointed out particularly. The scientific novelty consists in the defi- nition of the main problems, place and significance of each element of the legal impact mechanism in the social medium, taking into account the perception of legal awareness and legal culture as the centuries-old wealth of the people, which allows society to develop sustainably in difficult situations and even survive with- out shocks in certain difficult periods. It is noted that the majority of researchers study the legal culture of society, somewhat forgetting about the legal culture of each individual A proposal is made to create special advisory and informational state bod- ies, associations, public organizations and institutions for the practical im- plementation of state tasks in the field of culture and law in general, for informing and advising the population, considering the legal culture both in a narrow and broad conceptual sense, paying attention to the study of the functions of legal culture.